Student perceptions about nuclear plants and radioactive waste - Gombrade, Rafael [UNESP]; Londero, Leandro [UNESP] (Univ Francisco Jose Caldas, Fac Science & Education, 2022)
We present the results of a survey that analyzes the perceptions of a group of students about nuclear power plants and atomic waste. That is an excerpt from the largest project culminating in a master's thesis by the first author. Students' perceptions are associated with the risk of catastrophes that nuclear facilities can cause and the consequences of radioactive exposure on the human body. These perceptions are associated with information obtained through print or television news, television programs, movies, documents, and streaming series that deal with nuclear energy. Both news and television productions reinforce or stereotype fears regarding the risks of radiation and radioactivity. The results of our study can be useful for physics or chemistry teachers in the teaching of ionizing radiation. We argue discussions on this topic in classroom, in such a way, misunderstandings are minimized, and students adopt ideas and concepts of the Physics of ionizing radiation.
Keywords: Physics Sciences; Basic education; Analysis of Texts